Pelatihan Strategi Marketing Untuk Meningkatkan Penjualan Pada UMKM Nursa Di Kelurahan Rabadompu Kota Bima - Ayu Wandira; Titin Khalidah ; Tasya Radena Putri ; Ira Fauziah ; Ita Purnama (Institut Teknologi dan Bisnis Semarang, 2024)
UMKM are productive businesses owned by individuals or business entities that meet the criteria as micro-enterprises. With the current development of UMKM having great potential for economic development in Indonesia, the economic growth of UMKM is not accompanied by the capabilities of the UMKM players. There are still many UMKM who do not realize the importance of implementing a marketing strategy for the development of their business, for this reason there is a need for training and assistance to simplify the marketing implementation process. It is difficult for UMKM to develop due to their inability to compete with the rise of competitors both online and offline. This method of implementing community service aims to increase sales of Bima's typical product, namely Nursa herbal medicine, by providing assistance in creating a logo, creating a brand name, developing packaging and developing social media. The stages in carrying out this activity are observation, planning, discussion, implementation. Monitoring and evaluation. Having a brand name will make people familiar with the products sold by UMKM Nursa and by using social media it will make product sales easier.